Contemporary approaches to the study of religion: in 2 vol ; Vol. 2: The Social Sciences - Whaling, Frank (Religion and Reason, 2019)
Frontmatter -- Contents -- Preface -- I. Introduction / Whaling, Frank -- 2. Psychological Approaches / Wulff, David M. -- 3. Sociological Approaches (i) / Hill, Michael -- 4. Sociological Approaches (2) / Kehrer, Günter / Hardin, Bert -- 5. Social Anthropological Approaches / Jackson, Anthony -- 6. Cultural Anthropological Approaches / Oosten, Jarich -- 7. Cultural Anthropology and the many Functions of Religion / Beek, Wouter E.A. Van -- The Authors -- Index of Names of Scholars -- General Index